2005
DOI: 10.1109/clustr.2005.347075
|View full text |Cite
|
Sign up to set email alerts
|

Service Level Agreement based Allocation of Cluster Resources: Handling Penalty to Enhance Utility

Abstract: Jobs submitted into a cluster have varying requirements depending on user-specific needs and expectations. Therefore, in utility-driven cluster computing, cluster Resource Management Systems (RMSs)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(66 citation statements)
references
References 10 publications
1
58
0
Order By: Relevance
“…Both reward and penalty must be agreed at negotiation time and must be defined specified in the SLA. Penalty can be specified in SLA as a penalty function [27], which not only penalizes the provider for service failures but also compensates the users for them. An example of a reward and the penalty function is as follows:…”
Section: Penalties and Rewardsmentioning
confidence: 99%
“…Both reward and penalty must be agreed at negotiation time and must be defined specified in the SLA. Penalty can be specified in SLA as a penalty function [27], which not only penalizes the provider for service failures but also compensates the users for them. An example of a reward and the penalty function is as follows:…”
Section: Penalties and Rewardsmentioning
confidence: 99%
“…Large-scale scientific or engineering applications are usually mapped onto multiple distributed resources, so how to provide an efficient strategy without complicated coordination is a hard problem. Considering grid resource owners being similar to rational market participants, economic model becomes a topic of great interest in grid task scheduling strategies which are designed similarly to market supply-demand mechanisms [2] [3]. Although the grid resource provider, also being the scheduling decision maker, usually attempts to obtain maximum commercial profits, it has to design a seemingly fair allocation strategy since an obvious unreasonable allocation will arouse users' dissatisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of alternative economic strategies [4][5][6] and failure scenarios [1] have shown that small variations in key system variables can lead to large differences in overall system performance. While large-scale simulations are more practical than operational testbeds, computational expense can increase dramatically with model size, a critical factor for studying large-scale systems such as the Internet.…”
Section: Introductionmentioning
confidence: 99%
“…(1,1) 0.680000 (1,2) 0.020000 (1,4) 0.020000 (1,5) 0.020000 (1,6) 0.040000 (1,7) 0.040000 (1,9) 0.020000 (1,11) 0.020000 (1,13) 0.040000 (1,14) 0.040000 (1,15) 0.020000 (1,17) 0.020000 (1,18) 0.020000 (2,24) 0.040000 (2,25) 0.020000 (2,28) 0.020000 (2,29) 0.020000 (2,31) 0.020000 (2,34) 0.020000 (2,35) 0.020000 (2,36) 0.020000 (2,38) 0.020000 (2,41) 0.020000 (2,42) 0.020000 (2,43) 0.020000 (2,44) 0.020000 (2,…”
mentioning
confidence: 99%